Morphology of the megaspore Lagenoisporites magnus (Chi and Hills 1976) Candilier et al. (1982), from the Carboniferous (lower Mississippian: mid-upper Tournaisian) of Bolivia - Quetglas, Marcela Alejandra (2019)
The morphology and structure of megaspores assigned to Lagenoisporites magnus from the Toregua Formation, Retama Group, mid-upper Tournaisian of Bolivia were studied. The analysis was performed with light, fluorescence and scanning electron microscopy. Megaspores were laterally compressed and presented a spherical body with a proximal gula, of the hologula type. Gula had verrucae ornamentation and the spore body presented complex processes consisting of a bulbous base and an internally partitioned projection with sharp apex. In addition to this main ornamentation, perforations were present throughout the spore surface. Megaspores showed well marked curvaturae perfectae due to the abrupt transition existing between the gula ornamentation and the spore body processes. These megaspores were assigned to heterosporous arborescent lycopsids of the Lepidocarpaceae family, as in section view, exospore structure presented a three-dimensional network of fused elements. Likewise, due to a similarity found between sporoderm and Isoetes L. structure, it is evident that megaspores structure has remained intact inside the heterosporous lycopsids. Therefore; the L. magnus structure not only would confirm its affinity with the Lycophyta fossils but also with the living ones.